PENGARUH MOTIVASI KERJA DAN KEPEMIMPINAN SERTA KEAHLIAN PROFESIONAL DAN BUDAYA ORGANISASI TERHADAP KINERJA HAKIM AD-HOC PADA PENGADILAN NEGERI PALEMBANG - Natakusuma, Robert Irwan (Universitas muhammadiyah palembang, 2013)
This research aims to know the influence of work motivation and leadership, then also the influence of professional skill and culture of organization, to the work performance of ad-hoc judges in the state court of Palembang City. The design which is used to develop the research was cross-section design. There were 25 judges selected based on the census as the source of data research. There were 5 variables used and each of them was developed to several dimensions and indicators. Therefore, the main data of this research is the primary data with questonnaire as the collection method. Following this, the analysis method is multiple linear regression. The result of hypothesis testing is 1) there is a significant influence of work motivation,leadership, professional skill, and culture of organization to the work performance of ad-hoc judges; 2) It is partially proven that only work motivation and professional skill which influence significantly to the ad-hoc judge performance.